Diskursus Etika Aristoteles dalam Islam - Ahmad Habibi (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2020)
Ethics has always been an interesting subject to be discussed. It is not only its theoretic culture that contains rich values, but Ethics is also an applied science that touches the social behavior among the community directly. The urgency of ethics becomes a sensitive issue since it connotes good, bad, right, or wrong values. To explore the treasury of Ethics in the past time, in this case in The Before Christ (BC) century, is very interesting since the era is known as the Pre-Scientific era which refers to a condition of humans were still far from modern scientific traditions. However, Ethics has developed even becoming a value measurement for living both theoretically and practically at that time even in a different form. This research examined more deeply about Aristotle`s thoughts who lived in the BC Century. Although as a figure of Western Philosophy, Aristotle became a very influential figure in the Islamic world, especially Islamic figures of the Peripatetic School, such as Al Kindi, Al Farabi, and Ibn Sina. This research was a Library Research that attempted to reveal the construction and paradigm of Ethical values of Aristotle through his work entitled The Nichomachean Ethics. The ethical concept was reflected in the concept of Ethics in Islam as represented by Islamic Ethics Figures. The result found that the most fundamental difference between Aristotle and Islamic Ethics are ethical formulations. Aristotle's ethical formulation is realistic-materialism. For Aristotle, Goodness, Virtue, and Happiness are not abstract values, but all of them are real as empirical conditions. While Islam put ethics on two dimensions at once, they are realistic-materialism and theoretical-spiritualism.